2016
DOI: 10.1007/s00464-016-5238-6
|View full text |Cite
|
Sign up to set email alerts
|

The surgical outcomes of robot-assisted laparoscopic pancreaticoduodenectomy versus laparoscopic pancreaticoduodenectomy for periampullary neoplasms: a comparative study of a single center

Abstract: RPD is more efficient and secure process than LPD among properly selected patients. RPD is therefore a feasible alternative to the laparoscopic procedure. Further studies are needed to evaluate the cost effectiveness of the robotic approach for PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 26 publications
4
74
0
2
Order By: Relevance
“…Robotic surgery is thought to be superior to laparoscopy in different disciplines, including urological,[22] gynecological,[23] colorectal,[24] gastric,[25] and distal pancreatic operations,[26] but none have compared RPD to LPD in a large study,[19] as few institutions perform this complex operation using minimally invasive techniques, and the majority have adopted one approach versus the other, preventing single institutional comparison. The robotic platform provides a magnified three-dimensional image, 7 degrees of freedom, and eliminates hand tremor and the fulcrum effect of rigid laparoscopic instruments—allowing for precise suturing, easier tissue handling, better control of large blood vessels, and the ability to work at angles not possible with the laparoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robotic surgery is thought to be superior to laparoscopy in different disciplines, including urological,[22] gynecological,[23] colorectal,[24] gastric,[25] and distal pancreatic operations,[26] but none have compared RPD to LPD in a large study,[19] as few institutions perform this complex operation using minimally invasive techniques, and the majority have adopted one approach versus the other, preventing single institutional comparison. The robotic platform provides a magnified three-dimensional image, 7 degrees of freedom, and eliminates hand tremor and the fulcrum effect of rigid laparoscopic instruments—allowing for precise suturing, easier tissue handling, better control of large blood vessels, and the ability to work at angles not possible with the laparoscope.…”
Section: Discussionmentioning
confidence: 99%
“…[2–14] The majority of these reports showed that MIPD has at least equivalent postoperative and oncological outcomes compared to OPD but few studies have compared laparoscopic (LPD) versus robotic pancreaticoduodenectomy (RPD) to determine which minimally invasive platform may be best to adopt more broadly. [14–19]…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery presents notable advantagesand revolutionizes minimally invasive surgical approaches. Robotic technology improves many aspects of laparoscopy, including by providing three‐dimensional vision, enhancing dexterity and precision, eliminating surgeons' physiologic tremors, and simulating the wrist …”
Section: Introductionmentioning
confidence: 99%
“…Robotic technology improves many aspects of laparoscopy, including by providing threedimensional vision, enhancing dexterity and precision, eliminating surgeons' physiologic tremors, and simulating the wrist. [12][13][14][15] The last critical step of the radical operation is the Roux-en-Y hepaticojejunostomy. The small, deep and fixed operative field is a limitation for laparoscopy, especially when microsurgical…”
mentioning
confidence: 99%
“…Currently, there is no one standard RPD procedure and for the most part, RPD procedures depend on the surgeon’s experience . Recently, we published our own techniques and demonstrated the learning curve for RPD . RPD procedures differ to open PD surgical techniques, particularly in the reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%